Assembling and Characterizing a Simple Tapping-Actuated Triboelectric Nanogenerator as a Pedagogical Tool for Introductory Electronic Circuits (2023)
Since 2012, when triboelectric nanogenerators (TENGs) were first reported by Wang and co-workers, various applications have taken advantage of the TENGs ability to transform mechanical energy into electrical energy. TENG applications cover a wide range of fields such as electronics, physics, materials science, and engineering. The difference in the language used in the different research fields makes the understanding of results rather challenging for experts outside the fields. This article provides an introductory approach to triboelectric nanogenerators by assembling a Paper and packing Tape TENG by applying an Inquiry-Based Learning strategy. This will allow researchers new to the TENG field to become familiar with the terminology and basic concepts required for the understanding of electrical circuits related to TENG devices. The experiments were performed using LEDs, resistors, and capacitors by characterizing the output voltage and current with a view toward potential applications.